Body mass index and depressive symptoms in older adults: a cross-lagged panel analysis. - Jinseok Kim; Jin-Won Noh; Jumin Park; Young Dae Kwon (PLoS ONE, 2014)
There are conflicting results about the association between body mass index (BMI) and depressive symptoms in older adults. The present study examined the relationship between weight and depressive symptoms over time in older adults in South Korea.We used data from three waves of the Korean Longitudinal Study of Aging and ran a series of cross-lagged panel models to test the reciprocal relationship between depressive symptoms and obesity in older Korean adults. We assumed a temporally stable relationship between depressive symptoms and obesity and, thus imposed equality constraints over time.After controlling for the effect of depressive symptoms two years prior, underweight older adults had a higher depressive symptom score than those of normal weight. When controlling for obesity status from two years prior, older adults with higher levels of depressive symptoms were more likely to be underweight and less likely to be overweight than normal weight. The same patterns were observed in data from 2006 to 2008 and from 2008 to 2010.These results show that there is a correlation between depressive symptoms and weight status. In middle-aged and elderly Asian populations, depression can lead to weight loss rather than obesity, and underweight may develop depressive symptoms.